Comparison of CT, MRI, and F-18 FDG PET/CT for initial N-staging of oral squamous cell carcinoma: a cost-effectiveness analysis - Burian, Egon; Palla, Benjamin; Callahan, Nicholas; Pyka, Thomas; Wolff, Constantin; von Schacky, Claudio E.; Schmid, Annabelle; Froelich, Matthias F.; Rübenthaler, Johannes; Makowski, Marcus R.; Gassert, Felix (European journal of nuclear medicine and molecular imaging, 2022)
Treatment of oral squamous cell carcinoma (OSCC) is based on clinical exam, biopsy, and a precise imaging-based TNM-evaluation. A high sensitivity and specificity for magnetic resonance imaging (MRI) and F-18 FDG PET/CT are reported for N-staging. Nevertheless, staging of oral squamous cell carcinoma is most often based on computed tomography (CT) scans. This study aims to evaluate cost-effectiveness of MRI and PET/CT compared to standard of care imaging in initial staging of OSCC within the US Healthcare System.